On the Oriental leafhopper genus Takagioma Thapa, 1989 (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini) with descriptions of six new species - Qin, Huimin; Kang, Juxia; Huang, Min; Zhang, Yalin (Zootaxa, 2020)
The leafhopper genus Takagioma Thapa, 1989 is recorded from China for the first time. Six species, T. pagoda Kang and Zhang, T. rostra Qin and Huang, T. gladius Kang and Zhang, T. curvata Kang and Zhang, T. anguis Qin and Huang and T. longicuada Qin and Huang spp. nov, are described and illustrated. A check-list and a key to all species of Takagioma are provided.